РОБОТА НАД ПОТЕНЦІЙНИМ ЛЕКСИЧНИМ МАТЕРІАЛОМ ПРИ НАВЧАННІ ЧИТАННЯ ТЕКСТІВ ЗА ФАХОМ ДОРОСЛИХ УЧНІВ (Педагогіка вищої та середньої школи, 2022)
The article suggests methods of teaching potential vocabulary as one of the ways of enlarging the lexical stock of adult learners, the peculiarities of development of their memory and cognitive processes being taken into consideration.